OPTIMALISASI PROGRAM KESEHATAN IBU DAN ANAK MELALUI PENGUATAN FASILITAS KESEHATAN DAN KOMPETENSI TENAGA MEDIS: STUDI LITERATUR - Gunawan Widjaja (JOURNAL OF COMMUNITY DEDICATION, 2025)
Optimising maternal and child health (MCH) programmes is an important effort to reduce maternal and infant mortality rates and improve the quality of health services. This study uses a literature review approach to examine the role of strengthening health facilities and medical personnel competence in the success of MCH programmes. Data were collected from various reliable sources such as scientific journals, government reports, and world health organisation documents. The findings indicate that adequate health facilities equipped with standard infrastructure and facilities, along with competent and continuously trained medical personnel, are key factors in improving the coverage and quality of MCH services. Synergy between facility strengthening and enhancing the competence of medical personnel can result in more effective, responsive, and equitable services, thereby positively impacting the reduction of maternal and infant mortality rates. This study recommends an integrative strategy that includes infrastructure improvement, continuous training, intensive supervision, and strengthening of referral systems and service management as efforts to optimise MCH programmes in Indonesia.